Modern Dimensional Analysis-Based Heat Transfer Analysis: Normalized Heat Transfer Curves - Száva, Ioan; Vlase, Sorin; Száva, Ildikó-Renáta; Túrzó, Gábor; Munteanu, Mihaela Violeta; Gălățanu, Teofil-Florin; Asztalos, Zsolt; Gálfi, Botond-Pál (MDPI, Mathematics, 2023)
In this contribution, the authors continued their initial study on the efficiency of the analysis of experimentally obtained temperature curves, in order to determine some basic parameters that are as simple and reliable as possible, such as “m”, the heat transfer coefficient. After the brief review of the previous results, on which the present article is based, the authors offered a brief argumentation of the importance of dimensional methods, especially the one called modern dimensional analysis, in these theoretical-experimental investigations regarding the propagation of the thermal field of structural elements with solid sections, and especially with tubular-rectangular sections. It could be concluded that modern experimental investigations mostly follow the behavior of models attached to the initial structures, i.e., prototypes, because there are clear advantages in this process of forecasting the behavior of the prototype based on the measurement results obtained on the attached model.
Keywords: experimentally obtained temperature distribution law; relative temperature curves; m parameter’s variation laws; 2D steel structural elements; testing bench; reduced-scale models